Carex mazuilingensis (Cyperaceae), a new sedge from Hainan Island of South China - Yang, Hu-Biao; Dong, Shu-Peng; Wang, Qing-Long; Chen, Jin-Hua; Wu, Yuan-Yuan (Phytotaxa, 2026)
A new species of Carex sect. Radicales, C. mazuilingensis, from Hainan, South China, is described and illustrated. The new species is similar to C. planiscapa, but differs in its much longer leaves and culms, wider culms (ca. 3 mm), sheath-like involucral bracts with extremely degenerate blade, inflorescence with solitary obovoid to broadly ovoid and densely flowered spike, ca. 6 mm long and densely pubescent utricles, and ca. 5 mm long nutlets with a ca. 1.5 mm long stipe at base.